MODEL EFEKTIVITAS IMPLEMENTASI K3 DI FASILITAS NUKLIR: INTEGRASI STANDAR BAPETEN DAN BUDAYA KESELAMATAN KERJA - Ridwan Taufik Hidayat; Umi Rusilowati; Hamsinah B; Fitri Marsela; Taswanda Taryo (Journal of Innovation Research and Knowledge, 2026)
Abstract: This study aims to formulate an effectiveness model for Occupational Safety and Health (OSH) implementation at the G.A. Siwabessy Multipurpose Reactor (RSG-GAS) Facility by integrating the regulatory standards of the Nuclear Energy Regulatory Agency (BAPETEN) with the reinforcement of safety culture. Using a qualitative approach with a case study design, data were collected through technical document reviews, field observations, and in-depth interviews with key personnel. The results indicate that the effectiveness of the OSH system cannot be achieved solely through administrative regulatory compliance. Instead, it requires an integrated model where BAPETEN standards serve as the structural framework, while safety culture acts as the operational driver. The critical determinants of this model's effectiveness include high-level management commitment, worker situational awareness, two-way safety communication, and the consistent application of field procedures. The study concludes that the ideal effectiveness model in a nuclear facility is a synergy between compliance-based safety and behavior-based safety. These findings are expected to serve as a strategic reference and an evaluation model for nuclear facility managers to enhance worker protection standards and facility security sustainably.